2021
DOI: 10.1108/ijse-07-2020-0452
|View full text |Cite
|
Sign up to set email alerts
|

On the determinants, gains and challenges of electronic banking adoption in Nigeria

Abstract: PurposeThe purpose of this study is to examine the gains, challenges and determinants of electronic banking adoption in Nigeria.Design/methodology/approachThis paper applied the generalized structural equation modelling (GSEM) to a large sample of respondents surveyed from five of the six geopolitical zones of Nigeria to model the determinants of electronic banking. In addition to many other advantages, GSEM can be used as a likelihood function. As a result, this paper proposes GSEM as the most appropriate too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…For this reason, it is important to devote more energy to it as it transitions to more mature stages of development (Komulainen and Saraniemi, 2019;Shankar et al, 2020a;Singh and Srivastava, 2020;Tam and Oliveira, 2017a). Previous research has tended to remain focused on the determinants of m-banking adoption (Aduba, 2021;Chaouali et al, 2020;Elhajjar and Ouaida, 2020;Kumar et al, 2022), whereas scant research has been devoted to the post-adoption phase (Tam and Oliveira, 2017a).…”
Section: Mobile Banking Service Quality 1501mentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, it is important to devote more energy to it as it transitions to more mature stages of development (Komulainen and Saraniemi, 2019;Shankar et al, 2020a;Singh and Srivastava, 2020;Tam and Oliveira, 2017a). Previous research has tended to remain focused on the determinants of m-banking adoption (Aduba, 2021;Chaouali et al, 2020;Elhajjar and Ouaida, 2020;Kumar et al, 2022), whereas scant research has been devoted to the post-adoption phase (Tam and Oliveira, 2017a).…”
Section: Mobile Banking Service Quality 1501mentioning
confidence: 99%
“…, 2020a; Singh and Srivastava, 2020; Tam and Oliveira, 2017a). Previous research has tended to remain focused on the determinants of m-banking adoption (Aduba, 2021; Chaouali et al. , 2020; Elhajjar and Ouaida, 2020; Kumar et al.…”
Section: Introductionmentioning
confidence: 99%
“…It was focused on the United Nations records, on a significant achievement in terms of world-wide reduction in the level of poverty, improvement in basic education enrolments, women empowerment and awareness and gender equality (Oleribe & Taylor-Robinson, 2016). However, the millennium declaration did not achieve the set goals in Nigeria due to contextual factors such as the emergence of crises like the Boko Haram insurgency, the Niger Delta crisis and other economic challenges such as corruption (Aduba, 2021; Ojimba, 2012; Olujobi, 2021 a ; UNICEF, 2019). Other opposing challenges included neglect from the government, and strike actions by labour unions, lack of government commitment, girl child discrimination and poverty (Adepoju & Fabiyi, 2007; Alabi, Bahah, & Alabi, 2014; Dapo-Asaju & Bamgbose, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…All these studies did not examine the impact of cashless payment tools on the internet and mobile banking. Cashless payment was found to encourage internet and mobile banking (Kachathan & Chalchotchuang 2020 ; Aduba 2021 ). Urhie et al ( 2021 ) found mobile banking to promote cashless payments.…”
Section: Cashless Payment Internet Banking and Mobile Bankingmentioning
confidence: 99%
“…The diffusion of cash to cashless payment encouraged internet and mobile banking (Kachathan and Chalchotchuang 2020 ; Aduba 2021 ). Online debit and credit cards payments require transaction authorization code (TAC) from the bank.…”
Section: Diffusion Of Innovationmentioning
confidence: 99%